2014
DOI: 10.1017/s0033291714001123
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable cortico-striatal connectivity abnormalities in major depression in response to monetary gains and penalties

Abstract: Background Individuals with major depressive disorder (MDD) are characterized by maladaptive responses to both positive and negative outcomes, which have been linked to localized abnormal activations in cortical and striatal brain regions. However, the exact neural circuitry implicated in such abnormalities remains largely unexplored. Methods In this study 26 unmedicated adults with MDD and 29 matched healthy controls completed a monetary incentive delay task during functional magnetic resonance imaging (fMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 59 publications
4
48
0
Order By: Relevance
“…Functional imaging studies demonstrate depressionrelated hyporesponsivity in striatal areas (Epstein et al, 2006;Smoski et al, 2009) and disturbances in fronto-striatal connectivity (Furman et al, 2011). Deficits in brain activation and functional connectivity in basal ganglia substructures are suggested to normalize with different antidepressant treatments (Stoy et al, 2012;Admon et al, 2015). In ECT-treated patients, we recently showed a hyperconnectivity between the ventral striatum and ventral default-mode network, while simultaneously demonstrating hypoconnectivity with the anterior default-mode network, patterns that were modulated by ECT (Leaver et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…Functional imaging studies demonstrate depressionrelated hyporesponsivity in striatal areas (Epstein et al, 2006;Smoski et al, 2009) and disturbances in fronto-striatal connectivity (Furman et al, 2011). Deficits in brain activation and functional connectivity in basal ganglia substructures are suggested to normalize with different antidepressant treatments (Stoy et al, 2012;Admon et al, 2015). In ECT-treated patients, we recently showed a hyperconnectivity between the ventral striatum and ventral default-mode network, while simultaneously demonstrating hypoconnectivity with the anterior default-mode network, patterns that were modulated by ECT (Leaver et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies with this task revealed reduced striatal activation and functional connectivity in depressed versus healthy adults during anticipation and receipt of monetary reward (7, 26), making it well-suited for the present study (supplementary methods). …”
Section: Methodsmentioning
confidence: 99%
“…MDD patients generally exhibit reduced sensitivity to reward; this cognitive blunting is reflected by reduced ventral CSTC loop activation in the orbitofrontal cortex, anterior cingulate and ventral striatum to reward and loss receipt/anticipation (Smoski et al, 2011; Chantiluke et al, 2012; Schiller et al, 2013; Admon et al, 2015; Manelis et al, 2016). …”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…Connectivity between the putamen, caudate and cingulate during a monetary incentive delay task has been shown to predict response to psychotherapy (Admon et al, 2015; Walsh et al, 2016). High baseline ACC and low striatal activity were also shown to be predictive of improvement on antidepressants in a recent meta-analysis of 15 studies (Fu et al, 2013).…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%